Organic Insects Repellent From Essential Oils - Nawi, Adnin Afifi; Azmi, Mimi Nur Farhana; Nor Hassan, Najwa Syazwani; Akram Khan, Muhd Al-Hazim (Multidisciplinary Applied Research and Innovation, 2022)
In the market, many stores sell spray repellents that contain N, N-diethyl-meta-toluamide (DEET) for insect repellent but this chemical content can irritate the skin and give unpleasant odor to humans. In this study, organic ingredients such as cinnamon oil, tea tree oil, thyme oil, catnip oil and citronella oil were used. Cinnamon oil, tea tree oil, thyme oil and catnip oil were purchased from the market while citronella oil was extracted using Soxhlet extraction method in ethanol solvent. All of these essential oils were created with the intention of generating environmentally friendly repellents that could one day be a viable alternative to synthetic repellents due to their relative safety and low cost. The three formulations namely, Formulation 1, Formulation 2 and Formulation 3 were analysed for pH, enduring test and long-lasting skin rections. The results show that the pH were 4.0, 4.1 and 4.3 for Formulation 1, Formulation 2 and Formulation 3 respectively. It was also found that Formulation 3 is the best among the other two Formulations. For enduring test, ants, flies and mosquitoes were insects that have been used as experimental material. Ants would die directly when sprayed directly on them while flies and mosquitoes would stay away from the organic repellent spray. For long lasting reaction skin, most respondents stated the insect repellent liquid when exposed to the skin was in a cooling sensation for formulation 3 which is in pH 4.3. Therefore, further studies are needed to improve product function to provide optimal effectiveness to insects.